Pengaruh Pemberian Ekstrak Etanol Daun Dandang Gendis (Clinacanthus nutans (Burm F) Lindau) Terhadap Daya Analgetik Dan Gambaran Makroskopis Lambung Mencit - Maria Happy Christian Klau; Rosa Juwita Hesturini (Jurnal Farmasi & Sains Indonesia, 2021)
Dandang gendis (Clinacanthus nutans (Burm f.) Lindau) is one of the plants used for as medication for various type of illness. One of its uses is as an analgesic drug. This study aims to determine the effect of dandang gendis leaf extract on the analgesic activity and macroscopic image of the stomach of white rats. This research was conducted using a completely randomized unidirectional pattern. The creature used as treatment subjects were separated into five groups consists of five individual each: group I as negative control rats who were only given 1% Na-CMC equivalent, group II as positive control was given acetosal 500mg / KgBB, group III was given extract treatment with a dose of 450mg / KgBB, group IV was treated with the extract at a dose of 500mg / KgBB, group V was given an extract treatment at a dose of 550mg / KgBB. All groups were given acetic acid induction as a mediator of pain. The results showed that the ethanol extract of Dandang Gendis leaves had an analgesic effect and was safe to use as an analgesic at a dose of 500mg / KgBB.